1986
DOI: 10.1002/1097-0355(198622)7:2<132::aid-imhj2280070205>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal positive parenting: A follow-up evaluation

Abstract: In an earlier article (Boger, Richter, & Weatherston, 1983) the Perinatal Positive Parenting Program (PPP) was outlined. The basic tenets of the PPP program were discussed, and an overview of the in‐hospital, at‐home, and parents' support group components was provided. This article presents the results of a 15‐month follow‐up evaluation of treatment and control participants in the initial PPP demonstration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…Program participant mothers also had better maternal-infant relationships and more nurturing home environments at 12 months following NICU discharge than mothers in the comparison group. These findings are consistent with prior testing of the PPP program with a population of (Boger et al, 1986), and advance the general conclusion that support interventions have a positive impact on maternal and maternal-infant outcomes for families with highrisk infants (Affleck et al, 1991;Barrera et al, 1986;Ross, 1984). However, in past studies, professional providers of support were used.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Program participant mothers also had better maternal-infant relationships and more nurturing home environments at 12 months following NICU discharge than mothers in the comparison group. These findings are consistent with prior testing of the PPP program with a population of (Boger et al, 1986), and advance the general conclusion that support interventions have a positive impact on maternal and maternal-infant outcomes for families with highrisk infants (Affleck et al, 1991;Barrera et al, 1986;Ross, 1984). However, in past studies, professional providers of support were used.…”
Section: Discussionsupporting
confidence: 84%
“…Findings of a randomized study testing a parentto-parent model with full-term infants and their mothers identified better maternal-infant relationships and home environments for program participant mothers when their infants were 15 months of age (Boger, Richter, Kurnetz, & Haas, 1986). The program model, Perinatal Positive Parenting (PPP), was developed to provide support to first-time parents by trained, experienced, volunteer parents (Boger & Kurnetz, 1985).…”
mentioning
confidence: 99%
“…Ces dernières ont rapporté que les nouvelles mères étaient si préoccupées par leur bébé ou leurs problèmes personnels qu'elles n'avaient pas de temps à consacrer à une inconnue dont l'intérêt concernait les soins à l'enfant. Plus récemment, trois évalua-tions d'interventions post-natales par des paraprofessionnelles (Boger et al, 1986;Franks et al, 1987;Barth et al, 1988) auprès de familles à risque de mauvais traitements, n'arrivent pas à des conclusions évidentes, notamment à cause de la petite taille des groupes échantillonnés qui se rendent jusqu'à la fin de l'intervention.…”
Section: Intervenantes Non Professionnelles Et Prévention De L'enfancunclassified
“…Evaluations of family support/intervention programs have shown that these programs can make a difference for children and their families. For example, evaluations of several programs targeting infants and their parents found significantly higher HOME scores following program participation (Andrews et al, 1982;Boger, Richter, Kurnetz, & Haas, 1986; Clinton, Elwood, Parks, & Soraci, 1988). Other program results include positive changes in parents' use of control techniques, verbalization, and teaching strategies (Andrews et al, 1982;Gray & Ruttle, 1980;Slaughter, 1983).…”
Section: Implications For Infant Mental Healthmentioning
confidence: 99%